Dominant height growth and dynamic site index models for Crimean pine in the Kastamonu–Taşköprü region of Turkey - Seki, Mehmet; Sakici, Oytun Emre (Canadian Science Publishing, 2017)
Some dynamic site index models based on the generalized algebraic difference approach (GADA) were fitted for Crimean pine (Pinus nigra J.F. Arnold subsp. pallasiana (Lamb.) Holmboe) stands in Taşköprü, Turkey. Data were obtained from 132 dominant trees representing the wide range of site quality in the region. Nonlinear regression analysis and a second-order continuous-time autoregressive error structure were applied. After autoregressive modeling, the fitted models were evaluated both statistically and graphically. The best results were obtained with the dynamic site index model derived from the Bertalanffy–Richards base equation, accounting for about the 99% of the total variance in height–age relationships in dominant trees, with an Akaike information criterion (AIC) value of 119.55 and root mean square error (RMSE) of 0.5446. The selected base-age invariant dynamic site index curves provided the polymorphism with multiple asymptotes and other realistic height growth patterns.
Keywords: 15. Life on land; 16. Peace & justice